Stop the pain: Black and minority ethnic scholars on diversity policy obfuscation in universities. Issue 2 (5th February 2021) - Ahmet, Akile
Abstract : Purpose: The author extends the work on diversity policy in UK higher education by centring the voices of Black and minority ethnic scholars and de-centring white comfort with the aim of a call to stop the pain that sanitised university diversity policies cause Black and minority ethnic scholars. Design/methodology/approach: Using in-depth qualitative and auto-ethographic research methods, this paper engages with both respondents' narratives as well as the author's experience of carrying out the research within the walls of predominately white universities. Findings: In order for universities to move beyond hollow and sanitised diversity, they must centre the voices of Black and minority ethnic scholars. Respondents spoke of their experiences of pain, and feelings of "taking up" space in predominately white universities. The author also discusses respondents' feelings towards diversity and inclusion policies such as the Race Equality Charter Mark. Originality/value: The research is built on previous work on diversity by decentring white comfort.